Risks of all-cause and site-specific fractures among hospitalized patients with COPD - Liao, Kuang-Ming (Medicine (Baltimore), 2016)
Patients with chronic obstructive pulmonary disease (COPD) have a high prevalence of osteoporosis. The clinical sequel of osteoporosis is fracture. Patients with COPD who experience a fracture also have increased morbidity and mortality. Currently, the types of all-cause and site-specific fracture among patients with COPD are unknown. Thus, we elucidated the all-cause and site-specific fractures among patients with COPD. A retrospective, population-based, cohort study was conducted utilizing the Taiwan Longitudinal Health Insurance Database. Patients with COPD were defined as those who were hospitalized with an International Classification of Diseases, Ninth Revision, Clinical Modification code of 490 to 492 or 496 between 2001 and 2011. The index date was set as the date of discharge. The study patients were followed from the index date to the date when they sought care for any type of fracture, date of death, date of health insurance policy termination, or the last day of 2013. The types of fracture analyzed in this study included vertebral, rib, humeral, radial and ulnar/wrist, pelvic, femoral, and tibial and fibular fractures. The cohort consisted of 11,312 patients with COPD. Among these patients, 1944 experienced fractures. The most common site-specific fractures were vertebral, femoral, rib, and forearm fractures (radius, ulna, and wrist) at 32.4%, 31%, 12%, and 11.8%, respectively. The adjusted hazard ratios of fracture were 1.71 [95% confidence interval (95% CI) = 1.56–1.87] for female patient with COPD and 1.50 (95% CI = 1.39–1.52) for patients with osteoporosis after covariate adjustment. Vertebral and hip fractures are common among patients with COPD, especially among males with COPD. Many comorbidities contribute to the high risk of fracture among patients with COPD.